Vulvovaginal Infralevator Haematoma Mimicking the Second Stage of Labour - J. O. Awoleke; O. M. Ipinnimo (Hindawi Limited, 2017)
Even though they are quite uncommon, puerperal genital haematomas can be associated with serious maternal morbidity. Key findings are significant perineal pain and, depending on the location, visible swelling. However, attention can be drawn to its progression by the rare occurrence of persistent painful "bearing down" efforts, even after the successful delivery of the baby. The final size of this haematoma and the rare presentation make it truly uncommon. The primary goals of treatment include the prevention of further blood loss, minimizing tissue damage, relieving pain, and reducing the risk of infection. Management is generally conservative for small collections, but surgery is indispensable when they acutely expand in size or are large with worsening symptoms.